Development of Digital Transformation Strategies Based on Business Process Management Maturity Level Measurement at PT. Telkom Akses - Djatnika, Hendra Hadiyatna; Noviaristanti, Siska (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the business process management maturity of PT Telkom Akses amid digital transformation challenges in Indonesia’s telecommunications industry. Using a qualitative case study approach, data were collected through interviews, observations, and internal document analysis. The Business Process Management Maturity (BPMM) model was applied from both IT and BPM perspectives to assess the effectiveness of process management and identify areas for improvement. Findings indicate the current maturity level and highlight gaps in strategic alignment, governance, and IT support. The study provides recommendations to enhance operational efficiency and service quality, offering strategic insights for PT Telkom Akses and other telecom companies undergoing digital transformation.